Music as alchemy [journeys with great conductors and their orchestras] - Service, Tom (Faber, 2012)
How are conductors' silent gestures magicked into sound by a group of more than a hundred brilliant but belligerent musicians? The mute choreography of great conductors has fascinated and frustrated musicians and music-lovers for centuries, from Toscanini to Karajan, from Carlos Kleiber to Gustavo Dudamel. Orchestras can be inspired to the heights of musical and expressive possibility by their maestros, or flabbergasted that someone who doesn't even make a sound should be elevated to demigod-like status by the public. This is the first book to go inside the rehearsal rooms of some of the most inspirational orchestral partnerships in the world. It's the first to see how Simon Rattle works with his musicians at the Berlin Philharmonic, how Mariss Jansons deals with the Concertgebouw Orchestra in Amsterdam, and how Claudio Abbado creates the world's most luxurious pick-up band every year with the Lucerne Festival Orchestra. From London to Budapest, Bamberg to Vienna, great orchestral concerts are recreated as a collection of countless human and musical stories. The book reveals how the catalysts of place, time, and personal history are alchemised into the indelible magic of life-changing performances.